A History of Learning Communities Within American Higher Education. Issue 149 (March 2015) - Fink, John E.; Inkelas, Karen Kurotsuchi
Abstract : This chapter describes the historical development of learning communities within American higher education. We examine the forces both internal and external to higher education that contributed to and stalled the emergence of learning communities in their contemporary form.